Exploring Borrelia in Australia: Isolation, genomic characterisation, and host and vector associations - Alexander W. Gofton; Makenna Short; Michelle Michie; Dakota Gallaway; Ina Smith; Kim Blasdell; Anjana Karawita; Melissa J. Klein; Catherine A. Herbert; Stephen C. Barker (Ticks and Tick-Borne Diseases, 2025)
Borrelia are tick-borne spirochetes that include important pathogens that cause Lyme borreliosis and relapsing fevers. While multiple Borrelia species have been identified in Australia, further research is needed to understand their ecological roles and potential zoonotic risks. This study aimed to isolate and characterise two Australian Borrelia species—Borrelia tachyglossi and Borrelia sp. HB—through in vitro culture, genomic sequencing, and molecular surveys of ticks and vertebrate hosts. Despite extensive efforts, Borrelia sp. HB could not be cultured from Haemaphysalis bancrofti ticks, and its prevalence in questing ticks was low (0.14 %). Additionally, molecular screening of 504 wildlife hosts found no evidence of Borrelia sp. HB infection, suggesting a cryptic or highly restricted enzootic cycle. In contrast, B. tachyglossi was successfully cultured from Bothriocroton concolor ticks collected from echidnas (Tachyglossus aculeatus), enabling complete genome sequencing. Complement-mediated bactericidal assays demonstrated that B. tachyglossi is highly susceptible to human innate immunity, indicating it is unlikely to be pathogenic. Molecular surveys of wildlife-associated ticks revealed a broad diversity of reptile-associated Borrelia species in monitor lizards and snakes, reinforcing the hypothesis that Australian Borrelia persist in host-specific enzootic cycles. Our findings confirm that Borrelia species in Australia belong exclusively to the relapsing fever and reptile-associated clades, with no evidence of B. burgdorferi sensu lato. These results improve our understanding of Borrelia diversity in Australia and highlight the need for further research into their ecology, vector competence, and evolutionary history.